A variable‐stiffness continuum manipulators by an SMA‐based sheath in minimally invasive surgery. Issue 2 (17th February 2020) - Jiang, Surong; Chen, Bai; Qi, Fei; Cao, Yanfei; Ju, Feng; Bai, Dongming; Wang, Yaoyao
Abstract: Background: Due to its unique dexterity and safety, continuum manipulators have been widely used in small constrained environment. However, its flexibility also brings negative effects such as poor stiffness and low strength. This paper presents a novel variable‐stiffness sheath for continuum manipulators applied in minimally invasive surgery. Methods: We present a variable‐stiffness sheath based on shape memory alloy (SMA) for each module of the continuum manipulators. The stiffness of the sheath can be continuously adjusted depending on the voltage between both ends of the sheath, along with the phase transformation of SMA between austenite and martensite. Results: The experimental results demonstrate that the stiffness of the sheath and single module are able to increase up to 223.1% and 139.2%, separately, which verify the correctness of the proposed variable stiffness method. Conclusion: The robot integrated with the variable‐stiffness sheath is demonstrated to possess a fine capacity of variable stiffness.